The Status of Silver Carp Resources and Their Complementary Mechanism in the Yangtze River - Fang, Di-an; Zhou, Yan-feng; Ren, Peng; Peng, Yun-xing; Xue, Xiang-ping; Ren, Long; Xu, Dong-po (Frontiers in Marine Science, 2022)
The global climate and environmental variability can induce fish adaptive strategy change and form a corresponding complementary mechanism subsequently. Because of climate fluctuation, human activities, and water conservancy projects, it has been reported that natural fish resources of the silver carp have been declining in a wavy trend from 1950. However, few studies have explored the potential effects of determining the relationship between the adult fish and fish larvae. Using the field survey method, this study analyzed the fisheries resource status of the adult silver carp and its early life stage in the Yangtze River. Results indicated that different geographic populations showed significant habitat dependence, and the adult silver carp tends to choose habitats with slow water flow, rich biological bait, and less human interference. What is more, its distribution pattern has regional and seasonal differences obviously. Additionally, redundancy analysis on the fish larvae showed that water temperature and water flow are the two most important factors influencing the fish larvae blooming. According to the generalized additive model (GAM), the hydrological factors that significantly influence the larvae abundance are water temperature, transparency, daily increasing rate of water level, and discharge (p < 0.05). Combining the historical and present research data, the results indicated that river and lake connected habitat is essential for the silver carp recruitment and migration. Future studies should focus on the complementary mechanism of silver carp both in the natural habitat and invasion waters. It is suggested that the spawning habitat should be well protected during the channel project and economic belt construction along the Yangtze River.